Media experience and contemporary public relations practice: experiential accounts of selected practitioners - Mutetwa, Tatenda (Midlands State University, 2018)
This research is about media experience and contemporary Public Relations (PR) practice. It entails how media experience preferably as a journalist aids to the works of a PR practitioner. In the practice of contemporary PR there are skills that are therefore expected to package an ideal PR practitioner of today, this study then comes in to unveil them. There have been current developments in the practice of PR due to the advent of technology thus one has to keep abreast on the expectations of the industry.The research based on the publicity and stakeholder theory. A qualitative approach was used through a multiple case study. Interviews were used by the researcher to source out this information form various commendable contemporary PR practitioners in corporate organizations that have a well established reputation. The practitioners highlighted on the importance of media experience in contemporary PR practice, essential skills in PR and the internet revolution as a development in the practice of modern public relations. Through the study, the researcher recommends skills of success in PR which include good communication skills, writing and some technical aptitude.